Adenocarcinoma of the anal glands. - Behan, W M (1996)
Adenocarcinoma of the anal glands is very rare but it is an important lesion to recognise as with early diagnosis, it has an excellent prognosis. Because it involves the submucosa widely and penetrates the mucosa late, it can be mistaken for metastatic gastrointestinal carcinoma, or tumour arising in sinuses and fistulae. Two cases, in a 44 year old man and a 73 year old woman, which illustrate the typical features are reported, in one of which the diagnosis was missed originally. In situ neoplastic change of the associated anal glands and secretion of mucin lacking O-acetyl groups are useful pointers.